Local Fractional Functional Method for Solving Diffusion Equations on Cantor Sets - Yuan Cao; Wei-Gang Ma; Lian-Chuan Ma (Abstract and Applied Analysis)
The analytical solutions for the diffusion equations on Cantor sets with the nondifferentiable terms are discussed by using the local fractional functional method, which is a coupling method for local fractional Fourier series and Laplace transform.